Increasing economic openness of India, the purchasing power leakage and exchange rate effect - Rameshan, P. (2000)
This study represents a modest attempt to examine to what extent the economic openness of India affected the purchasing power leakage from the Indian economy occurring through its economic transactions with the rest of the world. The study compares the experience of Indian economy during 1990s with that during the closed 1970s and the mildly liberal 1980s in respect of the net trade flows, net factor income flows and net capital account flows and a host of other related parameters. The conclusion emerging from the analysis is that there is continued net purchasing power leakage from the Indian economy in many years even during 1990s. However, the leakage is much moderated during 1990s mainly due to the increased net capital account flows. At the same time, 1990s also witnessed a worsening external debt service scenario. A comparative evaluation of the empirical results for different sub-periods reveals that the relationship of net trade and net capital account flows with foreign exchange rate and other explanatory factors became weaker during 1990s. While this causes some surprise, this may also imply the need for making a more in-depth analysis, by incorporating several other factors, for explaining the various inflows of Indian economy during 1990s. - Reproduced
Keywords: Exchange rates - India; Exchange rates